Out of Sorts Translated by Wendeline Hardenberg - Valognes, Aurélie (Amazon Crossing, 2016)
Ferdinand Brun hasn’t always been a grumpy old man. Many years ago, he was a grumpy young man. Now he’d much rather spend time with his canine companion, Daisy, than any of his nosy neighbors. But as his behavior becomes increasingly peculiar, his daughter grows concerned and begins to consider moving him into a retirement home.In order to maintain his freedom, Ferdinand must submit to an apartment inspection by his longtime enemy, the iron-fisted concierge, Mrs. Suarez. Unfortunately, he’s never tidied up a day in his life. His neighbors, precocious ten-year-old Juliette and vivacious ninety-two-year-old Beatrice, come to the rescue. And once he lets these two into his life, things will never be the same. After an eighty-three-year reign of grouchiness, Ferdinand may finally learn that it’s never too late to start living.
Keywords: Aging; Fiction; Fiction; Families; Fiction; France; Fiction; Man-woman relationships; dept.lib; faculty_collection

Project Anastasis Translated by Wendeline Hardenberg - Vandroux, Jacques (Amazon Crossing, 2016)
As a former soldier, private investigator Jean Legarec is used to high stakes and sharpshooters. But he doesn’t realize what he’s getting into when he agrees to investigate the disappearance of six-year-old Alexandre, the grandson of a highly influential French politician.For a million euros, Legarec launches a dangerous search that will dig deep into some of the darkest corners of European history. With the help of the boy’s beautiful aunt, Béatrice, he uncovers evidence of a modern-day terrorist plot rooted in a long-buried enterprise of the Third Reich. From Paris to Malta to the Vosges forest, a cast of witnesses—including a death camp survivor and former mercenaries—help Legarec piece together a terrifying truth.Yet even then, the PI worries that his own dark past and his undeniable attraction to Béatrice might be clouding the investigation. Can he put the personal aside in order to do his job? And can he free an innocent child from a web of absolute evil?
Keywords: dept.lib; faculty_collection

And yet ... essays - Dickens, Jeffrey J. (Library Journal, 2016)
Keywords: dept.lib; ⛔ No DOI found

The politicians & the egalitarians: the hidden history of american politics - Dickens, Jeffrey J. (Library Journal, 2016)
Keywords: dept.lib; ⛔ No DOI found

The pragmatic superpower: winning the cold war in the middle east - Dickens, Jeffrey J. (Library Journal, 2016)
Keywords: dept.lib; ⛔ No DOI found

Tools of academic library assessment: the user survey - Liebst, Anne; Feinmark, David (Journal of Library Administration, 2016)
Academic libraries are taking a closer look at how well they are serving the needs of their users. As a result assessment activities become more important. In this column, the authors will focus on and describe one major tool of assessment—the user survey. © 2016, Published with license by Taylor & Francis.
Keywords: academic libraries; assessment; dept.lib; libraries—evaluation; library administration; library planning; user surveys